Religious Moderation in Indonesian Islamic Universities: Policy Implementation and Identity Formation at IAIN Ponorogo - Muhsin , M; Kususiyanah, Anjar; Maksum, Moh (Perkumpulan Alumni dan Santri Mahyajatul Qurro', 2024)
This study investigates the implementation of religious moderation policies in IAIN Ponorogo, Indonesia, and their impact on fostering social cohesion and cultivating a moderate identity within the academic community. Employing a qualitative case study methodology, data were collected through comprehensive interviews, Focus Group Discussions (FGD), and document reviews. The findings revealed significant progress in integrating religious moderation values into the curriculum, research activities, and community service programs. The establishment of the Religious Moderation House (RMB) has been instrumental in reinforcing these values through seminars, workshops, and outreach. However, challenges persist in achieving a consistent understanding and application of moderation principles among academic stakeholders. The survey results indicate that while a majority of students, faculty, and staff report positive changes in attitudes after participating in moderation programs, some individuals still struggle to fully grasp and internalize these values. Psychological and cultural factors, along with varying levels of commitment across faculties, present additional barriers to comprehensive adoption of a moderate identity. Despite these challenges, this study highlights the positive impact of religious moderation initiatives on promoting tolerance, reducing social tension, and preparing students for engagement with broader societal diversity. The findings emphasize the need for enhanced coordination, practical incentives, and continuous monitoring and evaluation to ensure the long-term sustainability and effectiveness of these programmes. By embedding religious moderation into its core strategic plans, IAIN Ponorogo could continue to empower its academic community to embody these values, thereby contributing to a more inclusive and harmonious educational environment.